Facile Synthesis of Mesoporous Silica for Separation of Coalbed Methane - Yang, Lusheng; Liu, Zhenghe; Zheng, Wenxiang (Asian Journal of Chemistry, 2014)
Mesoporous silica as potential adsorbent for separation of coalbed methane was prepared by using one anionic surfactant containing poly(ethylene oxide) group as template in a facile method. Small angle XRD, TEM and N2 adsorption-desorption isotherms were carried out to confirm the final product. From the results of characterizations, the diameters of the spherical particles have a narrow range of 100-130 nm and the mesoporous sizes are in 2-4 nm. In addition, the average pore size is 2.98 nm, the BET surface area is 572 m2/g and the pore volume is 0.4150 cm3/g.